Water Quality at Mokodou River as A Control River - Rohana Tair; Mohd Harun Abdullah; Hafizan Juahir; Baba Musta; Sahibin Abd Rahim; Fera Cleophas; Nur Zaida Zahari; Farrah Anis Fazliatul Adnan; Siti Aishah Mohd Ali; Kamsia Budin (Faculty of Science & Natural Resources, UMS, 2023)
The purpose of this study is to determine the water quality for Mokodou river to be suggested as control river for future research that related to ex-mining pollution at Ranau Sabah. The in-situ parameters were measured by using ProDSS YSI multimeter. And, for heavy metals the water samples were collected by using polyethylene bottles in depth between 15 to 20 cm under the surface water and preserve it with NHO3 until <pH 2 before analysed with ICPOES. The water quality parameters are measured were temperature, electrical conductivity (EC), DO, pH, turbidity, sulphate, chloride and heavy metals (Cu, Cr, Cd, Fe, Pb and Zn) with the concentrations 24.7 ± 2.03 oC, 91.24 ± 13.11 µS/cm, 8.21 ± 0.31 mg/L, 7.89 ± 0.35, 100.63 ± 216.96 NTU, 1.33 ± 1.21 mg/L, 8.61 ± 2.29 mg/L, 0.05 ± 0.05 mg/L, 0.01 ± 0.01 mg/L, 0.02 ± 0.01 mg/L, 0.45 ± 0.34 mg/L, 0.04 ± 0.01 mg/L and 0.03 ± 0.01 mg/L, respectively. The ANOVA one way shows that there is significant different between frequent sampling time (p< 0.05) except for sulphate and Pb. And, the water quality parameter at Mokodou river is still under the National Water Quality Standard for Malaysia (NWQSM) except for DO and turbidity. For conclusion, Mokodou river is identified as an unpolluted river that sugested to be control river for future research in Ranau area.